Dificuldades de aprendizagem que levam ao fracasso escolar nos anos iniciais do ensino fundamental - MARANI, Mara Kelcilene Sousa (2024)
This research has as its theme: Learning difficulties that lead to school failure in the early years of elementary school. School failure has been investigated in educational research to the extent that it is known for various aspects of the classification of students in the Brazilian school system. This factor transcends the momentary peculiarities of learning difficulties. In some cases, their striking causes have a socioeconomic origin, although they are not always determinant and are shown through the learning difficulty of the students, with their low levels of achievement. The objective of this research was to analyze the processes related to school failure and learning difficulties presented by children in the 5o year of elementary school. This is empirical research, and it is necessary to observe the context according to the descriptive qualitative methodology. Simplified, who was in charge of making an analysis of the processes related to school failure, in which it is centered on the student. Data collection occurred through semi-structured interviews, with subsequent systematization and exploratory analysis. A proposal for pedagogical intervention is presented with the teachers verifying the didactic performance with students who have learning difficulties. The phenomenological method was adopted, essentially descriptive and interpretative, with the purpose of describing and interpreting the phenomenon itself, as it presents itself. It was obtained the interpretation of the results that not overcoming school failure can become a life failure, since the absence of learning results in this stigmatization, one of the facets of the exclusion that permeates the school environment. Faced with such difficulties, he may be deprived of receiving a cultural heritage, which would lead him to understand and act better in the world in which he lives.